2020
DOI: 10.1177/2047173420922506
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of empirical studies on citizenship education in Latin America 2000 to 2017 and research agenda proposal

Abstract: This article will be of interest to anyone wishing to conduct research related to citizenship education in Latin America. It shares the results of a systematic review of empirical studies with the goal of (a) mapping the current research on citizenship education in Latin America and (b) suggesting a research agenda for citizenship education in Latin America. One particular contribution of this article is that it describes research that was previously accessible only to those who read Spanish. Findings include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A review of the most relevant keywords revealed that information literacy, ICT, communication, cooperation, and digital content production were the most frequent terms associated with digital skills. However, photographs, objects, audio or audio/visual items, and digital citizenship are the methods used in digital citizenship (Bramwell, 2020;Manzuoli et al, 2019;Richardson et al, 2021;Villalobos et al, 2021;Zhao et al, 2021). Existing research categorizes these methods into five categories, as stated above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the most relevant keywords revealed that information literacy, ICT, communication, cooperation, and digital content production were the most frequent terms associated with digital skills. However, photographs, objects, audio or audio/visual items, and digital citizenship are the methods used in digital citizenship (Bramwell, 2020;Manzuoli et al, 2019;Richardson et al, 2021;Villalobos et al, 2021;Zhao et al, 2021). Existing research categorizes these methods into five categories, as stated above.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this review focused on the methods used for digital citizenship. In other technical environments, no research on the appropriate use of digital technology has been done (Bramwell, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This is not to suggest that other methods have no value in understanding citizenship education, for controlled trials are certainly limited in their explanatory power, scope, and scalability, but controlled trials represent a frequent omission in the current evidence base which is difficult to compensate through other methods. Campbell (2019) points precisely to this in a recent literature review entitled "What Social Scientists Have Learned About Citizenship Education", and similar reviews by Bramwell (2020) and Manning and Edwards (2014) are also suggestive of a lack of controlled trials. As no systematic review of controlled trials within this area has yet been undertaken, we do so here for explorative purposes, to see how many studies of this kind exist and what aspects of Citizenship Education they address.…”
Section: Introductionmentioning
confidence: 90%
“…The first of these research areas, education's civic and citizenship function, is undoubtedly the largest The interest in investigating how prospective and active teachers perceive concepts such as citizenship and democracy is considerable (see, e.g., Anderson et al, 1997;Estelles and Romero, 2019;Faden, 2012;Hahn, 2015;Logan, 2011;Marri et al, 2014;Martin, 2008Martin, , 2010Patterson et al, 2012). In some cases, studies have dealt with teachers' ways of viewing the meaning of good citizenship (Bramwell, 2020;Martin et al, 2013;Prior, 1999). In other cases, the starting point has been a comparative study of teachers' perceptions of citizenship in different countries (Hung, 2013;Martínez-Rodríguez et al, 2019) or the identified gap between what citizenship teachers describe as their ideals and the actual teaching practices observed by researchers (Cohen, 2016).…”
Section: Previous Researchmentioning
confidence: 99%